Chronologia powstawania prebend w kapitule kieleckiej - Poniewozik, Leszek (Archiwa, Biblioteki i Muzea Kościelne, 2011)
The aim of this article is to present the early days of the formation of the Collegiate Chapter in Kielce. The analysis of the source material indicates that the Chapter of Kielce was founded in the 12th century on the basis of the revenue of the St. Adalbert Church in Kielce. At the beginning all the members of the corporation lead a community life (vita communis), but over time the assets of the Chapter was divided by separating particular prebendaries. This reorganization took place probably at the beginning of the 13th century. Perhaps this event occurred in 1213. In any case it happened before the year 1229. As a result of the reorganization 7 or 8 prebendaries were created. The earliest prebendaries were all prelatures, that is, provostry, custody, decania, scholasteria. Three or four canonic prebendaries were part of the Chapter and it is certain that the canonry, called the Jewish one, created in 1213 was among them. The others are probably the prebendaries of Pierzchnica, Brzechów and Szydłowiec. The late medieval composition of the Chapter comprising 4 prelatures and 6 canons was completed, in time, by the canons called Szewno and Sieradowice. The first one was created in the middle of the 13th century, and the other one between 1327 and 1350. As it has been mentioned above, the creation of the Chapter of Kielce was connected with the acquisition of the property of St. Adalbert Church. The income derived from it was, however, too meager to meet the needs of all the prelates and canons. In the light of the late medieval sources it can be assumed that the revenue of the St. Adalbert Church was used to create only 2 prelatures (custodia and scholasteria) and 2 canons (Pierzchnica and Brzechów). The pay for other prebendaries came from other sources. It is assumed that the main founders-if not the only ones-were the Bishops of Kraków.